A millennium of cold-water coral habitat loss in the East Pacific during low ENSO variability in the mid- to late Holocene - Joseph A. Stewart; Laura F. Robinson; Michelle L. Taylor; Daniel J. Fornari; Katleen Robert; Stuart Banks; Tianyu Chen; Tao Li; James Kershaw; Shannon Hoy; Qian Liu; Jessica D. Gordon; et al. (Proceedings of the National Academy of Sciences, 2026)
The evolution of El Niño–Southern Oscillation (ENSO) under past and future climate change and its influence on marine ecosystems is highly debated. To examine links between tropical climate variability, high-latitude feedbacks, and deep-sea ecosystems, we have analyzed over 900 subfossil cold-water scleractinian corals from the Galápagos Archipelago. U-Th dating shows that these corals have inhabited the region for at least 117,000 y, thriving at depths down to ~1,000 m. However, we find a millennial-scale gap in coral occurrence ~5,000 y ago, coinciding with reduced ENSO variability and a persistent La Niña-like state. Coral presence resumed as ENSO cyclicity strengthened again toward modern conditions. While shallow-water coral growth has been shown to generally decline in the equatorial Pacific during El Niño surface warming, the mid- to late Holocene loss of cold-water corals may reflect the opposite: prolonged La Niña-like conditions. We hypothesize that stronger upwelling at this time intensified the oxygen minimum zone, adversely affecting cold-water coral habitats. With ENSO projected to change under continued ocean warming, the potential vulnerability of cold-water corals to future climate change is a growing concern. This study underscores the value of understanding past ENSO behavior and its impact on deep-sea ecosystems in a warming world.